An Evidence-Based Approach to the Diagnosis and Management of Seborrheic Dermatitis: A Systematic Review - Lisa Anggraini (International Medical Journal Corp. Ltd, 2026)
Introduction: Seborrheic dermatitis (SD) is a prevalent, chronic inflammatory skin disorder with a significant impact on patient quality of life. Its pathogenesis is multifactorial, involving an interplay between Malassezia yeast, host immune response, and skin barrier integrity. While numerous treatments exist, an updated synthesis is needed to integrate novel therapies into the clinical management algorithm. This systematic review aims to critically appraise and synthesize high-level evidence from randomized controlled trials (RCTs) on the efficacy and safety of interventions for SD in adolescents and adults. Methods: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted to identify RCTs evaluating pharmacological or procedural interventions for SD. Studies were selected based on pre-defined inclusion criteria. Data on study design, patient characteristics, interventions, and outcomes were extracted. The methodological quality of included studies was assessed using the Cochrane Risk of Bias tool. Results: Seventeen RCTs met the inclusion criteria. The evidence confirms the efficacy of first-line topical therapies, including antifungals (ketoconazole, ciclopirox) and anti-inflammatory agents (corticosteroids, calcineurin inhibitors). Ketoconazole 2% formulations are consistently superior to vehicle (e.g., treatment success of 25.3% vs. 13.9%, P=0.0014) and prophylactic use reduces relapse. Ciclopirox demonstrates non-inferiority and, in some cases, superiority to ketoconazole in maintenance phases. The novel phosphodiesterase-4 (PDE-4) inhibitor, roflumilast 0.3% foam, demonstrated significantly higher rates of Investigator Global Assessment (IGA) Success compared to vehicle at week 8 (79.5% vs. 58.0%; P<0.001) with a favorable safety profile. For recalcitrant disease, oral itraconazole was significantly more effective than placebo in improving severity scores (P=0.023) and reducing recurrence (P=0.003). Other therapies, including lithium salts and tea tree oil, also showed significant efficacy in controlled trials. Discussion: The therapeutic landscape for SD is evolving from a primary focus on microbial control to a dual approach that also targets host inflammation. The high efficacy and safety of roflumilast foam, the first new mechanism of action approved for SD in over two decades, facilitates a paradigm shift from reactive flare management to proactive, long-term maintenance of clearance without the risks of chronic corticosteroid use. Conclusion: The management of SD should be stratified based on disease severity and location. Topical antifungals and the novel PDE-4 inhibitor roflumilast represent effective and safe first-line options. Short-term topical corticosteroids are useful for managing acute flares, while calcineurin inhibitors serve as steroid-sparing alternatives. Systemic antifungals are reserved for severe, refractory cases. This review provides an evidence-based framework to guide clinicians in optimizing therapeutic strategies for this chronic condition.